A new sinoalid froghopper in mid-Cretaceous amber from northern Myanmar (Hemiptera, Cicadomorpha, Sinoalidae). (September 2021) - Fu, Yanzhe; Szwedo, Jacek; Huang, Diying
Abstract: Here we describe and illustrate a new genus and species of the extinct froghopper family Sinoalidae, Cretomultinervis burmensis gen. et sp. nov. from Burmese (Myanmar) amber. The new genus can be recognized from all sinoalids by the combination of an enlarged pronotum, hind tibia armed with five interlaced lateral spines, leaf-shaped tegmen with very broad postcostal cell, basal cell extremely long, hindwing with costal margin armed with 5 micro-spines basally, and cross vein mp-cua apparently basad of stem CuA fork. This peculiar combination of primitive and derived characters suggests that Cretomultinervis likely represents an early-diverging lineage of Sinoalidae, increasing our knowledge on the morphological disparity of this extinct family during the late Mesozoic.